On the type locality of Sorubim trigonocephalus Miranda-Ribeiro, 1920 (Siluriformes: Pimelodidae) - Ohara, Willian Massaharu; Neuhaus, Emanuel Bruno (Zootaxa, 2016)
Sorubim trigonocephalus was described in 1920 by Alípio de Miranda Ribeiro, based on a single specimen collected in a locality identified as “Porto Velho”, during the "Comissão das Linhas Telegráficas Estratégicas de Mato Grosso ao Amazonas” (more commonly known as Rondon Commission). Given that the type locality is Porto Velho, the species has been referred to the Madeira River basin (Lundberg & Littmann, 2003; Littmann, 2007; Eschmeyer et al., 2016). Nevertheless, after its description, no additional specimens were collected in the Madeira basin despite several ichthyological expeditions undertaken to the area (Santos, 1996; Camargo & Giarrizzo, 2007; Rapp Py-Daniel et al., 2007; Perin et al., 2007; Pedroza et al., 2012; Casatti et al., 2013; Queiroz et al., 2013a), some of them including region of Porto Velho (Fowler, 1913; Araújo et al., 2009; Torrente-Vilara et al., 2011; Queiroz et al., 2013b).